PARALLEL FRAMEWORK OF MUá¸¤AMMAD AND MOSESS STORY: AN ANALYSIS OF THE NARRATIVES OF á¸¤ALÄªMAH AL-SAÊ¿DIYYAH - Azmi, Ahmad Sanusi (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2018)
Kajian modern tentang asal-usul sÄ«rah Nabawiyah telah menelusuri dan menemukan keberadaan pengaruh kitab suci sebelumnya dan unsur-unsurnya dalam narasi sÄ«rah. Kisah tentang Halimah, sang ibu susuan, menurut Raven, menunjukkan kejadian paralel dengan kematangan Yesus ketika bayi, dalam Injil. Selain itu, para sarjana Muslim seperti Ibn Hisham ditemukan konsisten dalam membuat perbandingan paralel antara Muhammad dan Musa dalam karyanya. Tulisan ini memfokuskan pada kehidupan awal yang terfokus pada periode á¸¤alÄ«mah al-Sadiyyah dengan menganalisis penggunaan referensi Al-Quran dalam narasi. Penelitian ini bersifat kualitatif dengan metode pendekatan kritis dan analisis tekstual untuk membaca cerita. Kajian ini menemukan proposisi bahwa ada dua kemungkinan alasan yang mengarahkan Ibn Hisham menambahkan ayat 28:12 dari Al-Quran sebagai referensi atas catatan waktu Muhammad sebagai bayi yang menyusu. Isu pertama ketidakjelasan digital dalam narasi Ibn IsÄq. Dan yang kedua adalah memberikan kepercayaan kepada kisah kedua nabi, Muhammad dan Musa.Modern studies of the origin of sÄ«rah nabawiyyah have traced and suggested the existence of influence of previous scriptures and their elements within the sÄ«rah narrative. The extraordinary speed and marks of physical maturity in Prophet Muá¸¥ammadâs wet-nurse period with Halimah, which, according to Raven, indicates a parallel occurrence with Jesus precocity in the Gospels of the Infancy. Besides, Muslim scholars such as Ibn HishÄm was found to consistently make parallel comparison between Muá¸¥ammad and Moses in his work. This study aims to explore the narratives of Prophet Muá¸¥ammadâs early life, with special focus to his period with á¸¤alÄ«mah al-Saâdiyyah and analyse the use of Quranic reference in the narrative. The study is qualitative in nature in which the researcher employed critical and textual analysis to examine the story. The present study in its finding proposes that there are two possible reasons which lead Ibn HishÄm to adduce verse 28:12 of the Quran as his reference to the account of Muá¸¥ammadâs time as a suckling infant. The first is to elucidate lexical obscurity in the narration of Ibn Isá¸¥Äq. And the second is to give credence to the similarity between the accounts of two prophets, Muá¸¥ammad and Moses.